PREVALENSI CESTODIASIS SALURAN PENCERNAAN PADA KAMBING - Maryam Abusari (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The aim of this study was to determine the prevalence of gastrointestinal cestodiasis in goats. The sample collection was carried out in September-October 2019 in Tilongkabila and Kabila Bone Districts. Examination of feces samples used the Native method, Sedimentation and Flotation. A total of 3 samples of goat feces from Tilongkabila District, and 6 samples of goat feces from Kabila Bone District contained Cestoda worm eggs. The prevalence of Cestodiasis in goats in Tilongkabila District is: 3.5%. The presence of cestodiasis in goats obtained by the Natif method: 0%, precipitation: 2.3% and flotation: 1.2%. The prevalence of Cestodiasis in goats in Kabila Bone District was: 6.6%. The presence of cestodiasis in goats produced based on the Native method: 1.1%, Precipitation: 3.3% and Flotation